Relationship between attenuation of impact shock at high frequency and flexion-extension of the lower extremity joints during downhill running - Ryu, J.-S.; Yoon, S.-H.; Park, S.-K. (Korean Journal of Sport Biomechanics, 2016)
Objective: The purpose of this study was to determine the interrelationship between ranges of motion of the knee and ankle joints on the sagittal plane and the attenuation magnitude of impact shock at high frequency (9~20 Hz) in the support phase during downhill running. Method: Fifteen male heel-toe runners with no history of lower extremity injuries were recruited for this study (age, 25.07 ± 5.35 years; height, 175.4 ± 4.6 cm; mass, 75.8 ± .70 kg). Two uniaxial accelerometers were mounted to the tuberosity of tibia and sacrum, respectively, to measure acceleration signals. The participants were asked to run at their preferred running speed on a treadmill set at 0°, 7°, and 15° downhill. Six optical cameras were placed around the treadmill to capture the coordinates of the joints of the lower extremities. The power spectrum densities of the two acceleration signals were analyzed and used in the transfer function describing the gain and attenuation of impact shock between the tibia and the sacrum. Angles of the knee and ankle joints on the sagittal plane and their angle ranges were calculated. The Pearson correlation coefficient was used to test the relationship between two variables, the magnitude of impact shock, and the range of joint angle under three downhill conditions. The alpha level was set at .05. Results: Close correlations were observed between the knee joint range of motion and the attenuation magnitude of impact shock regardless of running slopes (p<.05), and positive correlations were found between the ranges of motion of the knee and ankle joints and the attenuation magnitude of impact shock in 15° downhill running (p<.05). Conclusion: In conclusion, increased knee flexion might be required to attenuate impact shock during downhill and level running through change in stride or cadence while maintaining stability, and strong and flexible ankle joints are also needed in steeper downhill running.